2003
DOI: 10.1353/rhe.2002.0034
|View full text |Cite
|
Sign up to set email alerts
|

The Roles and Challenges of Deans

Abstract: This study examined the relationships among the roles of college deans and conflict and ambiguity in deans' work. Challenges deans perceived as imminent in the future were also studied. The sample included 1,370 deans from 360 universities. They were asked about their roles, conflicts and ambiguities they faced, and possible challenges for the future. The responses show that deans are inevitably confronted with situations that require them to engage in roles that conflict with priorities that remain unfocused.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 35 publications
1
40
0
2
Order By: Relevance
“…The findings of the current study, and the studies of Montez, Wolverton, and Gmelch (2002), and La Lopa et al (2002) indicate that some of the greatest challenges for leaders were fiscal and fund-raising challenges. Furthermore, Montez et al (2002) also found issues-such as dealing with difficult personnel, moving faculty toward change, dealing with changing technology, and ensuring diversity of faculty and students-that had common ground with our study.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The findings of the current study, and the studies of Montez, Wolverton, and Gmelch (2002), and La Lopa et al (2002) indicate that some of the greatest challenges for leaders were fiscal and fund-raising challenges. Furthermore, Montez et al (2002) also found issues-such as dealing with difficult personnel, moving faculty toward change, dealing with changing technology, and ensuring diversity of faculty and students-that had common ground with our study.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, Montez et al (2002) also found issues-such as dealing with difficult personnel, moving faculty toward change, dealing with changing technology, and ensuring diversity of faculty and students-that had common ground with our study. La Lopa et al (2002) also found that participants believed technology would have the biggest impact in the future of the discipline.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Deans are responsible for academic quality within their unit, and fundraising is becoming an increasingly important part of the dean's job. (Wolverton, Gmelch et al 2001) A national study of academic deans identified six areas of a dean's responsibility: external and political relations, personal scholarship, leadership, resource management, internal productivity, and academic personnel management (Montez, Wolverton et al 2002). Another study of academic deans in research and doctoral institutions identified relationship building as a key component of successful leadership in higher education, and examined disciplinary differences among deans.…”
Section: What Do Deans Do?mentioning
confidence: 99%
“…In the management literature there are a number of studies examining the successful leadership attributes of academic deans in higher education (Montez et al . , Wepner et al . ).…”
Section: Introductionmentioning
confidence: 99%